Altered glial fibrillary acidic protein content and its degradation in the hippocampus, cortex and cerebellum of rats exposed to constant light: reversal by melatonin - Baydas, G; Reiter, RJ; Nedzvetskii, VS; Nerush, PA; Kirichenko, SV (Wiley, 2002)
Reactive astrocytosis is a well-known phenomenon that occurs rapidly after physical or metabolic injury to the brain. One of the important events during astrocyte differentiation is the increased expression of glial fibrillary acidic protein (GFAP), a member of the family of intermediate filament structural proteins. Free radicals are neurotoxic and free radical scavengers have been shown to protect the brain against neurotoxic damage. In the present study, we examined the effect of melatonin on astrocytic reactivity by determining the expression of the glial marker, GFAP, in different brain regions. Rats were exposed to constant light to reduce endogenous melatonin production; half of the animals were injected with melatonin during the exposure to constant light for 7 days. Western blots showed increases in total and degraded GFAP content in the brain of rats exposed to constant light. Melatonin admisnistration caused a reduction of degraded GFAP content. In addition, melatonin significantly reduced neural tissue lipid peroxidation while constant light significantly enhanced the breakdown of lipids in the brain. Brain glutathione levels decreased significantly as a result of constant light exposure; this reduction was reversed by melatonin administration. These results suggest that melatonin potentially protects both neurons and glial cells from free radicals; melatonin's protective actions are probably related to the antioxidant properties of the indole.
Keywords: antioxidant; astrocytes; constant light; free radicals; glial fibrillary acidic protein; melatonin